Mutu Pelayanan Kontrasepsi oleh Bidan di Polindes Desa Sukatali - Habibah, Gina Nurul; Hadi, Ella Nurlaella (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Family planning services are a human right and a key intervention in improving the health of women and children. The tendency to use private service facilities for contraceptive services is increasing compared to government service facilities. Factors that influence it are services that are still of low quality, limited contraceptives, and the lack of provision of service facilities and infrastructure in the regions. This study aims to describe the quality of contraceptive services by midwives at Pondok Bersalin Sukatali Village in 2021. This study was a Rapid Assessment Procedure (RAP) by conducting in-depth observations and interviews with selected informants by purposive sampling. Interviews were conducted with one village midwife and five disaster family acceptors. The results showed that the availability of facilities and infrastructure for contraceptive services had been fulfilled 95%, in addition to the contraceptive service equipment had been fulfilled 96%, and the availability of management facilities had been fulfilled 100%. Good services included history taking, preparation, implementation, and midwifery documentation. Meanwhile, there were still many family planning acceptors who did not get a complete physical examination, and counseling had not been given completely. The midwife's compliance with the standards was anamnesis = 93%, preparation = 100%, physical examination = 60%, implementation = 100%, counseling = 84% and midwifery documentation = 100%. Patient satisfaction at the Maternity Boarding School in Sukatali Village on the aspects of tangibility, responsiveness, assurance, was mostly in the good category. Meanwhile, in the aspect of reliability and empathy, most of them were in the sufficient category.Keywords: family planning; contraceptive services; midwife; quality ABSTRAK Pelayanan keluarga berencana merupakan hak asasi manusia dan suatu intervensi kunci dalam upaya meningkatkan kesehatan perempuan dan anak. Kecenderungan pemanfaatan fasilitas pelayanan swasta untuk pelayanan kontrasepsi meningkat dibanding fasilitas pelayanan pemerintah. Faktor yang mempengaruhinya adalah pelayanan yang masih kurang berkualitas, keterbatasan alat kontrasepsi, dan minimnya pengadaan sarana dan prasarana pelayanan di daerah. Penelitian ini bertujuan untuk mengetahui gambaran mutu pelayanan kontrasepsi oleh bidan di Pondok Bersalin Desa Sukatali pada tahun 2021. Penelitian ini merupakan Rapid Assessmenst Procedure (RAP) dengan melakukan observasi dan wawancara mendalam kepada informan yang dipilih secara purposive sampling. Wawancara dilakukan kepada satu bidan desa dan lima akseptor keluarga beencana. Hasil penelitian menunjukkan bahwa ketersediaan sarana dan prasarana pelayanan kontrasepsi di sudah terpenuhi 95%, selain itu peralatan pelayanan kontrasepsi sudah terpenuhi 96%, dan ketersediaan sarana manajemen sudah terpenuhi 100%. Pelayanan yang sudah baik antara lain anamnesa, persiapan, implementasi, dan dokumentasi kebidanan. Sementara itu, masih banyak akseptor keluarga berencana yang tidak mendapatkan pemeriksaan fisik secara lengkap, serta konseling juga belum diberikan secara lengkap. Pencapaian kepatuhan bidan terhadap standar adalah anamnesa = 93%, persiapan = 100%, pemeriksaan fisik = 60%, implementasi = 100%, konseling = 84% dan dokumentasi kebidanan = 100%. Kepuasan pasien di Pondok Bersalin Desa Sukatali pada aspek tangibel, responsivenes, assurance sebagian besar dalam kategori baik.   Sedangkan pada aspek relliability dan emphaty sebagian besar dalam kategori cukup.Kata kunci: keluarga berencana; pelayanan kontrasepsi; bidan; kualitas